2008
DOI: 10.1002/art.23719
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal body composition phenotypes in older rheumatoid arthritis patients: Association with disease characteristics and pharmacotherapies

Abstract: Objective. To compare measures of body fat and lean mass and the prevalence of abnormal body composition phenotypes (sarcopenia, overfat, and sarcopenic obesity) in men and women with rheumatoid arthritis (RA) versus matched controls, and to explore the disease-related predictors of abnormal body composition in patients with RA. Methods. A total of 189 men and women with RA and 189 age-, sex-, and race-matched non-RA controls underwent dual-energy x-ray absorptiometry for measurement of total and regional body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
186
5
11

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(214 citation statements)
references
References 28 publications
12
186
5
11
Order By: Relevance
“…On the other hand, patients with RA have higher percentages of fat mass compared to healthy controls, and this increase of fat mass can be undetected because it often coincides with a decrease of muscle mass and thus normal BMI (12,21). BMI is therefore not a good marker of body fat content because it does not distinguish between the tissues that comprise it.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, patients with RA have higher percentages of fat mass compared to healthy controls, and this increase of fat mass can be undetected because it often coincides with a decrease of muscle mass and thus normal BMI (12,21). BMI is therefore not a good marker of body fat content because it does not distinguish between the tissues that comprise it.…”
Section: Discussionmentioning
confidence: 99%
“…2 In previous studies, abnormalities in body composition (sarcopenia, overfat, and sarcopenic obesity) were reported to be greater in patients with RA than controls. 16 The adipose tissue is known as a producer of several pro-inflammatory cytokines, such as tumor necrosis factor-alpha, interleukin-6, and interleukin-1, all of which are associated with aging, obesity, and low muscle mass. 5 In our study, we could not demonstrate any significant relationship between muscle mass and disease characteristics, including disease duration, pain evaluation, morning stiffness duration, disease activity, and ages of the patients.…”
Section: Smimentioning
confidence: 99%
“…Decreased lean mass, extreme term "sarcopenia, " and increased fat are indicators of poor health in the general population. Loss of lean mass causes weakness, disability, and metabolic abnormalities (2). In most studies, body mass index (BMI), an index that evaluates body weight according to height, has been used as representative of BC.…”
Section: Introductionmentioning
confidence: 99%
“…In their cross-sectional analysis, Giles et al (29) reported that DMARD treatment alone, biologic or not, is associated with a reduction in the risk of abnormal BC. In our study, no association was found between steroid, DMARD, and biological agent use and sarcopenia development.…”
mentioning
confidence: 99%